Influence Customer Relationship Management and Store Atmosphere on Customer Loyalty at Baradjawa in Surabaya - Priananda, Arya Mahardika; Azizah, Nurul (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to determine and analyze the influence of customer service, customer interaction, store layout, and store appearance on customer loyalty in Baradjawa, Surabaya. In the increasingly tight business competition, maintaining good relationships with customers and creating a comfortable store atmosphere are important strategies to build customer loyalty. This study uses quantitative and survey methods. Data were obtained by distributing questionnaires to 126 active Baradjawa customers. The analysis technique used is multiple linear regression. The results of this study indicate that customer service, customer interaction, store layout, and store appearance together have a significant influence on customer loyalty. Customer service does not have a significant influence on customer loyalty. Customer involvement has a significant influence on customer loyalty. Then the store layout has a significant influence on customer loyalty. Finally, store appearance has a significant influence on customer loyalty.